Effect of holding a racket on propulsion technique of wheelchair tennis players. (27th May 2016) - de Groot, S.; Bos, F.; Koopman, J.; Hoekstra, A. E.; Vegter, R. J. K.
Abstract : The purpose of this study was to determine possible differences in propulsion technique between propelling the wheelchair with and without a racket in the hand. Eight experienced wheelchair tennis players performed three submaximal exercise tests and six sprint tests on a wheelchair ergometer. Torque and velocity were measured during the tests and power output and timing variables were calculated. Differences between the conditions with and without racket were analyzed. When propelling with the racket, the racket side showed a significantly lower push time ( P = 0.03), lower percentage push time ( P = 0.001), shorter contact angle ( P < 0.001), more power loss before ( P = 0.006) and after ( P = 0.001) the push, a higher peak ( P = 0.009) and mean ( P = 0.005) power output during the push, and a lower mean overall velocity ( P = 0.03). When the same hand is compared when propelling with and without racket or when the sprint data were analyzed, similar significant differences were found. Propelling the wheelchair while holding a racket has negative effects on the propulsion technique and may lead to injuries of the upper extremity. The longer time needed to couple the hand with the racket to the rim leads to higher power losses and subsequently higher power output generation during the shorter push phase.